Effects of Crude Oil Price Uncertainty on Fossil Fuel Production, Clean Energy Consumption, and Output Growth: An Empirical Study of the U.S. - Avazkhodjaev, Salokhiddin; Dhiensiri, Nont; Rakhimov, Eshmurod (International Journal of Energy Economics and Policy, 2024)
This study investigates the impact of crude oil price uncertainty on U.S. fossil energy production, clean energy consumption, and economic output growth from January 2000 to June 2024. Employing the Nonlinear Autoregressive Distributed Lag (NARDL) model, the analysis captures both short- term and long-term asymmetric effects among the variables. The findings reveal that crude oil price uncertainty exerts a significant negative influence on fossil fuel production in both the short and long terms. Conversely, while renewable energy consumption initially responds positively to crude oil price volatility in the short run, this effect becomes significantly negative over the long term. Additionally, crude oil price uncertainty consistently has a significant negative impact on output growth in both the short and long runs. The Generalized Impulse Response Function (GIRF) analysis within a Vector Autoregression (VAR) framework demonstrates that shocks to crude oil prices result in sustained declines in both fossil energy production and renewable energy consumption, with reductions of approximately −0.003% points within 5-6 months. The adverse effect on output growth intensifies over time, underscoring the prolonged economic repercussions of oil price uncertainty. The study highlights that linear models are insufficient for capturing the complexities of oil price volatility, as corroborated by Wald test results. In response to these findings, the study offers several policy recommendations to enhance economic stability. These include prioritizing energy source diversification to reduce reliance on volatile fossil fuels, establishing stabilization mechanisms such as strategic reserves and price stabilization funds, and fostering the transition to clean energy through increased investment and technological advancement. Furthermore, implementing counter-cyclical fiscal measures and investing in infrastructure can help stabilize the economy during downturns, while enhanced monitoring and forecasting capabilities are crucial for effectively managing oil price trends.